The semiotic approach in analyzing contemporary graphic text (Al-Academy, 2022)
With a great diversity in the curriculum contemporary monetary and visions, and development that hit the graphic design field, it has become imperative for the workers in the contemporary design research and investigation in accordance with the intellectual treatises and methods of modern criticism, because the work design requires the designer and recipient both know the mechanics of tibographic text analysis in a heavy world of texts and images varied vocabulary and graphics, and designer on before anyone else manages the process of analysis to know what you offer others of shipments visual often of oriented intended from behind, what is meant, in the midst of this world, the curriculum Alsemiae directly overlap with such diverse offerings it best suited for the analysis of what sends the text of the encryption in its structure, which is a comprehensive holistic approach operates with knowledge of modern, contemporary and text Graphic carries in its contents is much that should be studied and searched, that this world is a result, the world of graphic excellence, and the requirements of the current research sounding triggers graphic text Gore according to a method Semiaia clear entrances.